2019
DOI: 10.1016/j.ajhg.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Recent Adaptive Acquisition by African Rainforest Hunter-Gatherers of the Late Pleistocene Sickle-Cell Mutation Suggests Past Differences in Malaria Exposure

Abstract: The hemoglobin b S sickle mutation is a textbook case in which natural selection maintains a deleterious mutation at high frequency in the human population. Homozygous individuals for this mutation develop sickle-cell disease, whereas heterozygotes benefit from higher protection against severe malaria. Because the overdominant b S allele should be purged almost immediately from the population in the absence of malaria, the study of the evolutionary history of this iconic mutation can provide important informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…A recent study revisited the history of the balancing selection acting on the HBB gene in Africa and showed that the sicklecell mutation first appeared in the ancestors of present-day farmers more than 20,000 ya (Laval et al, 2019). It was then acquired by rainforest hunter-gatherers through adaptive admixture over the last 6,000 years.…”
Section: Cultural Transitions and Host Immune Adaptationmentioning
confidence: 99%
“…A recent study revisited the history of the balancing selection acting on the HBB gene in Africa and showed that the sicklecell mutation first appeared in the ancestors of present-day farmers more than 20,000 ya (Laval et al, 2019). It was then acquired by rainforest hunter-gatherers through adaptive admixture over the last 6,000 years.…”
Section: Cultural Transitions and Host Immune Adaptationmentioning
confidence: 99%
“…The inter-relationship between malaria parasites and human hosts is associated with adaptive mutations in the human genome. A recent study that focused on the evolution of human populations that were highly exposed to malaria provides an additional argument in favour of the association between deforestation and malaria 6 .…”
mentioning
confidence: 99%
“…It was recently found that homozygotes of βS sickle mutation can lead to sickle-cell disease while heterozygotes contribute to higher protection 33 . The heterozygotes of CHRNA4 polymorphism (rs1044396) showed higher activity during cognitive engagement than the homozygotes in the cingulo-opercular (CO) network 34 .…”
Section: Discussionmentioning
confidence: 99%